THE EVOLUTION OF ISLAMIC MEDICINE AND ITS IMPACT ON MODERN MEDICINE - Al-Naqbi, Mohamed (Al-Adab Journal, 2025)
This research aims to explore the evolution of Islamic medicine and its enduring impact on modern medicine. It examines how Muslim scholars contributed to the development of medical sciences since the eighth century AD by establishing methodologies based on experimentation, observation, and patient case analysis. The study also highlights the reciprocal influences between Islamic medicine and other civilizations, such as the European civilization, which relied on translating Islamic medical texts starting from the twelfth century AD. This translation facilitated the transfer of medical knowledge and influenced the foundations of Western medicine. Additionally, the research analyzes medical theories developed by scholars like Al-Razi and Ibn Sina in diagnosis and treatment, as well as surgical techniques introduced by Al-Zahrawi. The study demonstrates how many therapeutic principles and terms established by Islamic medicine still retain their significance in contemporary medicine, making this heritage an integral part of the historical evolution of medicine.